Proton play in the formation of low molecular weight chitosan (LWCS) by hydrolyzing chitosan with a carbon based solid acid - Krishnan, R. Akhil; Deshmukh, Pranjal; Agarwal, Siddharth; Purohit, Poorvi; Dhoble, Deepa Arun; Waske, Prashant; Khandekar, Dileep; Jain, Ratnesh; Dandekar, Prajakta (Carbohydrate Polymers, 2016)
Low molecular weight chitosan (LWCS) constitute a special class of value added chemicals that are primarily obtained from crustacean shells, which are the main water pollutants from crabs and shrimp processing centers. Unlike chitin and chitosan, LWCS possess improved solubility in water and aqueous solutions, making them widely applicable in numerous fields ranging from drug delivery to waste water treatment. Among the methods employed for their production, chemical breakdown by strong liquid acids has yielded good success. However, this method is met with severe concerns arising from the harsh nature of liquid acids, which may corrode the reactors for commercial synthesis, and their limited reusability. The physical methods like ultrasound and microwave are energy intensive in nature, while the enzymatic methods are expensive and offers limited scope for reuse. We have attempted to overcome these problems by employing carbon based solid acid (CSA) for hydrolyzing chitosan to LWCS. CSA can be easily produced using activated carbon, a cost-effective and easily available raw material. Reactions were carried out between chitosan and CSA in a hydrothermal glass reactor and the products, separated by cold centrifugation, were purified and dried. The dried products were characterized for their molecular weight and solubility. Results indicated more than ten-fold decrease in the molecular weight of chitosan and the product exhibited water solubility. The CSA could be used upto four times, without regeneration, to give a consistent quality product. The aqueous solution of resulting LWCS exhibited a pH of 6.03 +/- 0.11, as against the acidic pH range of solutions of commercially available LWCS, indicating its suitability for biomedical applications. Our investigation facilitates a `green approach' that may be employed for commercial production of value added chemicals from waste products of marine industry. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Carbon based solid acid; Chitosan; green synthesis; Hydrolysis; Low molecular weight chitosan

Enteric pH responsive cargo release from PDA and PEG coated mesoporous silica nanoparticles: a comparative study in Drosophila melanogaster - Sapre, Nidhi; Chakraborty, Rusha; Purohit, Poorvi; Bhat, Suresh; Das, Gaurav; Bajpe, Sneha R. (RSC Advances, 2020)
Physiological stimulus-specific cargo release from nanoparticle carriers is a holy grail of drug delivery research. While the majority of such work is carried out in vitro with cell lines, widespread use of common mammalian model systems - mice and rats - is difficult due to the associated cost and regulatory restrictions. Here we use the inexpensive, easily reared, excellent genetic model system Drosophila melanogaster to test pH responsive cargo release from widely used mesoporous silica nanoparticles (MSNs) coated with pH sensitive polydopamine (PDA) and polyethylene glycol (PEG) polymers. We synthesized 650 +/- 75 nm diameter PDA or PEG coated mesoporous silica nanoparticles loaded with a fluorescent dye and fed to individual adult flies. Subsequently, the passage of the particles were monitored through the fly gut. As in mammals, the fly intestine has multiple pH specific zones that are easily accessible for imaging and also genetic, biochemical or physiological manipulations. We observed that both the species of MSNs ruptured around the acidic (pH < 4.0) middle midgut of the flies. PEG coated particles showed sharper specificity of release in the acidic middle midgut of flies than the PDA coated ones and had less tendency to clump together. Our results clearly show that the Drosophila gut can be used as a model to test pH responsive biocompatible materials in vivo. Our work paves the way for greater use of Drosophila as an in vivo complete systemic model in drug delivery and smart materials research. It also suggests that such specific delivery of chemical/biological cargo can be exploited to study basic biology of the gut cells and their communication with other organs.